2013
DOI: 10.1002/jaba.63
|View full text |Cite
|
Sign up to set email alerts
|

Some indirect effects of positive practice overcorrection

Abstract: We evaluated the effects of positive practice overcorrection (PP OC) on levels of motor stereotypy and appropriate engagement in the activity practiced during treatment with 3 young men with autism. We also measured preference for the practiced activities during preference probes to determine if these activities might acquire aversive properties as a result of the frequent pairing with PP OC. Treatment reduced motor stereotypy for all 3 participants, and engagement increased for 2 of the 3 participants. Relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Falcomata et al () and Bartlett et al () found that NCR alone did not reduce inappropriate vocalizations and spitting, respectively, to clinically significant levels, and that the addition of response cost resulted in immediate decreases in problem behavior to near‐zero levels. Peters and Thompson () and Watkins and Rapp () found that NCR alone did not produce reductions in automatically reinforced stereotypy, whereas NCR combined with overcorrection (Peters & Thompson) or response cost (Watkins & Rapp) was effective in reducing stereotypy for all participants.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Falcomata et al () and Bartlett et al () found that NCR alone did not reduce inappropriate vocalizations and spitting, respectively, to clinically significant levels, and that the addition of response cost resulted in immediate decreases in problem behavior to near‐zero levels. Peters and Thompson () and Watkins and Rapp () found that NCR alone did not produce reductions in automatically reinforced stereotypy, whereas NCR combined with overcorrection (Peters & Thompson) or response cost (Watkins & Rapp) was effective in reducing stereotypy for all participants.…”
mentioning
confidence: 96%
“…Falcomata et al (2004) and Bartlett et al (2011) found that NCR alone did not reduce inappropriate vocalizations and spitting, respectively, to clinically significant levels, and that the addition of response cost resulted in immediate decreases in problem behavior to near-zero levels. Peters and Thompson (2013) and Watkins and Rapp (2014) found that NCR alone did not produce reductions in automatically reinforced stereotypy, whereas NCR combined with overcorrection (Peters & Thompson) or response cost (Watkins & Rapp) was effective in reducing stereotypy for all participants. Differential reinforcement using an arbitrary reinforcer (e.g., an edible or leisure item) has also been found effective for treating automatically reinforced problem behavior (Ringdahl et al, 2002;Taylor, Hoch, & Weissman, 2005;Toussaint & Tiger, 2012); however, researchers have demonstrated the need for additional punishment components before clinically significant outcomes are observed (Anderson & Le, 2011;Baker et al, 2010;Mitteer, Romani, Greer, & Fisher, 2015).…”
mentioning
confidence: 99%
See 3 more Smart Citations